FUNDING FOR SCIENCE AND RESEARCH ABROAD: EXPERIENCE FOR UKRAINE (Вісник: Міжнародні відносини, 2021)
The article analyses the problems of promoting innovation in different countries under conditions of information society. It is the innovation process, which involves intelligence, experience, knowledge, and values, that allows many countries to benefit from these advantages and achieve high rankings in global competition. As innovation becomes a powerful driver of economic growth and international competitiveness, national governments pay special attention to the challenges of scientific and technological development by focusing financial, intellectual and research resources on these targets.To ensure the innovative development, different countries of the world mobilize domestic resources – financial, human, intellectual, and creative capital, business potential, and attract external factors – international scientific and technical cooperation, international alliances, multinational corporations, global value chains and others. The conditions of global competition produce changes in the set of factors that support innovative growth and competitiveness of nations in the world markets. Proper funding of research and development becomes one of the most important factors among them.These problems are especially relevant for Ukraine, as the innovative development model might drive the country to a new technological level, support sustainable economic growth and competitive position in the global innovation market, as well as create new jobs in new science-intensive industries, which boost employment and prosperity.
Keywords: information society, innovative development, funding scientific research and development, funds, grants